2021
DOI: 10.3855/jidc.14381
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices for the use of seasonal influenza vaccination, healthcare workers, Costa Rica

Abstract: Introduction: Annual seasonal influenza vaccination in healthcare workers prevents nosocomial transmission to patients, coworkers, and visitors, and reduces absenteeism. This study aimed to describe knowledge, attitudes, and practices (KAP) of seasonal influenza vaccine among public healthcare workers attending patients in Costa Rica. Methodology: We conducted a cross-sectional survey of healthcare personnel attending patients in public hospitals in 2017–2018. Frequency distributions of demographics, vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Overall, about 60% of HCP infrequently received influenza vaccines over an eight-year period; this population with low influenza vaccine uptake was primarily physicians and HCP who worked in an outpatient setting. Similar trends in low influenza vaccination coverage have been seen among HCP in KAP studies in Honduras [17] , Costa Rica [18] , Egypt [19] , and parts of the Middle East [20] . This low coverage was also seen in the general HCP population recruited into this study but excluded from analysis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Overall, about 60% of HCP infrequently received influenza vaccines over an eight-year period; this population with low influenza vaccine uptake was primarily physicians and HCP who worked in an outpatient setting. Similar trends in low influenza vaccination coverage have been seen among HCP in KAP studies in Honduras [17] , Costa Rica [18] , Egypt [19] , and parts of the Middle East [20] . This low coverage was also seen in the general HCP population recruited into this study but excluded from analysis.…”
Section: Discussionsupporting
confidence: 67%
“…To increase vaccination uptake, hospitals could decrease barriers to vaccination by increasing availability of convenient times or places to receive vaccines. Lack of time to receive a vaccine was repeatedly reported as a barrier to vaccination in prior KAP studies in similar settings [17] , [18] , [20] and was found to be the main driver for infrequent vaccination among people reporting barriers to vaccination. Currently in Peru, influenza vaccination for HCP is not mandated by employers and campaigns vary by location; some hospitals coordinate cars to bring vaccines to HCP locations, while others offer drop-in vaccination at hospitals.…”
Section: Discussionmentioning
confidence: 86%
“…On the contrary, HCWs in studies carried out in Greece and Costa Rica reported that concern about the effectiveness of flu vaccines was the most common barrier among other factors to flu vaccination [ 62 , 63 ]. However, these studies reported low, suboptimal, and decreasing influenza vaccine coverage in HCWs, despite their positive attitudes toward the influenza vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on the knowledge, attitude, and practice (KAP) of healthcare professionals, pregnant women, travelers, and general workers towards influenza virus and vaccination in different countries and regions [ 14 , 15 , 16 , 17 ]. A satisfactory level of knowledge related to COVID-19 and its prevention among the Italian elderly was found [ 18 ], which promised a positive attitude and practice towards vaccination.…”
Section: Introductionmentioning
confidence: 99%